Indigenous Land Right in Brazil: A comparison between the letter of the law and it’s applications - Becker, Priscila B. (Ciência & Trópico, 2013)
RESUMO A Comissão Interamericana de Direitos Humanos (CIDH) é um importante órgão do Sistema Interamericano através do qual comunidades indígenas podem denunciar abusos cometidos por Estados contra seus direitos humanos. Em outubro de 2002, a CIDH recebeu uma denúncia contra a República Federativa do Brasil por supostas violações ao direito à propriedade e às garantias e proteção judiciais consagrados na Convenção Americana sobre Direitos Humanos e em prejuízo do povo indígena Xucuru e seus membros, na cidade de Pesqueira, PE. O presente artigo coloca referido caso em contexto e investiga a aplicação dos direitos indígenas a seus territórios na prática. Parte I contém um breve resumo do caso. Parte II introduz o leitor aos direitos indígenas na legislação brasileira e explica o processo de demarcação de terras. Parte III contrasta a legislação com a maneira como ela é aplicada na prática, focalisando em: (1) ocupações e invasões de terras indígenas e (2) a tensão entre reconhecimento dos direitos indígenas e desenvolvimento econômico. Parte IV conclui o artigo. PALAVRAS-CHAVE: Comunidades indígenas. Direitos humanos. Processo de demarcação de terras. ABSTRACT The Inter-American Commission on Human Rights (IACHR) represents an important venue where indigenous peoples can denounce human rights abuses committed within States. In October of 2002, a petition was lodged with the IACHR on behalf of the Xucuru indigenous peoples and against the Federative Republic of Brazil for alleged violations of the rights to property, to a fair trial, and to judicial protection guaranteed in the American Convention on Human Rights. The present paper provides a contextual background to the case and examines the application of indigenous land rights in Brazil as they exist on paper. Part I of the paper provides a summary of the case. Part II provides the legal framework for the protection of indigenous land rights and explains the demarcation process of indigenous lands, including current developments. Part III contrasts the letter of the law with its actual application, and focuses on two obstacles to the full realization of indigenous people’s rights to their traditional lands as they exist on paper: (i) non-indigenous occupation and invasion of indigenous lands; and (ii) the tension between the recognition of indigenous rights and economic development. Part IV provides a conclusion to the investigation. KEYWORDS: Indigenous peoples. Human rights. Land demarcation.